The Lamanites Portrayed in the Book of Mormon - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
The Lamanites in the Book of Mormon are descendants of the Nephite, Mulekite, and Lamanite peoples. They were a scourge to the Nephites to keep them faithful to the Lord. They survived because they observed the Lord's commandments regarding marriage. When the elder Mosiah and his followers left, the remaining body of Nephites were probably either destroyed or became Lamanites. Once the Lamanites understood the Lord's word, they were very faithful and renounced their previous living style. Out of this milieu came Samuel, the Lamanite prophet.